Development of Problem-Based Mathematics Learning Media in the Independent Curriculum - Febry Fajar Nurvicky; Moh Mahfud Effendi; Reni Dwi Susanti (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
This study aims to develop mathematics learning media with the Microsoft Office 365 Powerpoint program, the Problem-Based Learning model assisted by the TikTok application in an independent curriculum. In developing this learning media, researchers used the ADDIE development type (Analysis, Design, Development, Implementation, and Evaluation) with 30 students as respondents in mathematics at MTS Muhammadiyah 1 Malang. Data collection techniques were in the form of questionnaires which included observation and interview questionnaires, media and material validation questionnaires, as well as pre-test and post-test questionnaires. The feasibility test Assessment by material experts includes learning objectives, learning methods, learning resources, learning activities, and learning materials, 77% of which are categorized as very feasible. Then the media was tested in the class before and after being given the media test treatment. The results were 0.028 with the treatment category before and after using the TikTok application-based learning media. In this case, it means that the mathematics learning media combined with the TikTok application is very feasible to use.